Microscopic origin of near- and far-field contributions to tip-enhanced optical spectra of few-layer MoS2. Issue 40 (11th October 2021) - Kroth, Kathrin; Klement, Philip; Chen, Limei; Chatterjee, Sangam; Klar, Peter J.
Abstract : Far-field effects depending on microscopic structure, tip, and environment dominate tip-enhanced optical spectra of 2D materials such as MoS2 . Abstract : Tip-induced optical spectroscopy overcomes the inherent resolution limits of conventional optical techniques enabling studies of sub-nm sized objects due to the tip's near-field antenna action. This statement is true for individual molecules on surfaces or in the gas phase, but does not hold without restrictions for spatially extended samples. The reason is that the perturbations caused by the tip extend into the sample volume. The tip may induce strain, heating or hot-carrier injection locally in the material. These effects add additional degrees of complexity by changing near-field and far-field optical response. The far-field response varies because strain relaxation, heat and carrier diffusion possess areas of influence exceeding the sample area influenced by the short-range near-field effects. Tip-in spectra are not simply enhanced compared to tip-out spectra, they will also vary in spectral appearance, i.e., peak positions, relative peak intensities, and linewidths. Detailed studies of MoS2 samples ranging from a single layer to bulk-like multi-layer MoS2 also reveal that the spectra are sensitive to variations of phonon and band structure with increasing layer number. These variations have a direct impact on the signals detected, but also clearly modify the relative magnitudes of the contributions of the tip-induced effects to the tip-in spectra. In addition, the optical response is affected by the kind of tip and substrate used. Hence, the presented results provide further insight into the underlying microscopic mechanisms of tip-enhanced spectroscopy and demonstrate that 2D materials are an ideal playground for obtaining a fundamental understanding of these spectroscopic techniques.